2021
DOI: 10.1101/2021.07.29.454400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Habit formation viewed as structural change in the behavioral network

Abstract: Habit formation is a process in which an action becomes involuntary. While goal-directed behavior is driven by its consequences, habits are elicited by a situation rather than its consequences. Existing theories have proposed that actions are controlled by these two distinct systems. Although canonical theories based on such distinctions are starting to be challenged, there is no theoretical framework that implements goal-directed behavior and habits within a single system. Here, we propose a novel theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(228 reference statements)
0
1
0
Order By: Relevance
“…The facts lead us to assume that there can be a different principle from maximizing a single reward, as expected in a laboratory setting. Evidence for this has long been reported in animal behavior research, such as engaging in diverse behaviors not related to the experimental task (Breland and Breland, 1961; Falk, 1966; Gentry, 1968; Levitsky and Collier, 1968; Skinner, 1948), and changes in the relative reward effects of behavioral opportunities, such as a less preferred behavior reinforce a more preferred behavior under specific environmental settings (Allison and Timberlake, 1974), have been reported, and it has been theoretically suggested that task-unrelated behaviors influence the behavior of task-related behaviors Theories suggest that they may influence task-related behavioral behavior (Baum, 2012; Guthrie, 1930; Herrnstein, 1970; Killeen and Fetterman, 1988; Staddon, 1979; Timberlake and Allison, 1974; Yamada and Toda, 2023). In addition, we showed that behavioral changes caused by motivational operation to HRL were similar to those of animal operant behaviors (Podlesnik et al, 2006; Shull, 2004; Shull et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The facts lead us to assume that there can be a different principle from maximizing a single reward, as expected in a laboratory setting. Evidence for this has long been reported in animal behavior research, such as engaging in diverse behaviors not related to the experimental task (Breland and Breland, 1961; Falk, 1966; Gentry, 1968; Levitsky and Collier, 1968; Skinner, 1948), and changes in the relative reward effects of behavioral opportunities, such as a less preferred behavior reinforce a more preferred behavior under specific environmental settings (Allison and Timberlake, 1974), have been reported, and it has been theoretically suggested that task-unrelated behaviors influence the behavior of task-related behaviors Theories suggest that they may influence task-related behavioral behavior (Baum, 2012; Guthrie, 1930; Herrnstein, 1970; Killeen and Fetterman, 1988; Staddon, 1979; Timberlake and Allison, 1974; Yamada and Toda, 2023). In addition, we showed that behavioral changes caused by motivational operation to HRL were similar to those of animal operant behaviors (Podlesnik et al, 2006; Shull, 2004; Shull et al, 2001).…”
Section: Resultsmentioning
confidence: 99%